2003
DOI: 10.1175/1520-0442(2003)016<0734:fotoao>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Features of the Observed Annual Ocean–Atmosphere Flux Variability on the West Florida Shelf

Abstract: The annual cycle of sea surface temperature and ocean-atmosphere fluxes on the west Florida shelf is described using in situ measurements and climatology. Seasonal reversals in water temperature tendency occur when the net surface heat flux changes sign in boreal spring and fall. Synoptic-scale variability is also important. Momentum and heat flux variations result in successive water column stratification and destratification events, particularly at shallower depths during spring. Fall is characterized by des… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 29 publications
0
19
1
Order By: Relevance
“…4). The WFS is characteristically affected by extratropical fronts from October through June (e.g., Virmani and Weisberg 2003). Although all possible combinations between moorings were examined for many other time periods, the observations shown in Fig.…”
Section: Observationsmentioning
confidence: 99%
“…4). The WFS is characteristically affected by extratropical fronts from October through June (e.g., Virmani and Weisberg 2003). Although all possible combinations between moorings were examined for many other time periods, the observations shown in Fig.…”
Section: Observationsmentioning
confidence: 99%
“…Upwelling is known to occur seasonally around the Gulf, over the shallow Campeche banks, the northeastern Gulf coast, and the west Florida shelf. Compensating coastal downwellings probably also occur (Virmani and Weisberg 2003). It is thus impossible to accurately close the mass balance or to know which of the competing mass fluxes is more correct.…”
Section: A Gulf Of Mexicomentioning
confidence: 99%
“…Lower [CHL] surf values are observed from May to July and maximum values are found in winter from December to February. This cycle is considered to be primarily triggered by annual changes in ocean-atmosphere fluxes (Virmani and Weisberg, 2003), resulting in the deepening of the mixed layer in winter. In the GOM, it has been suggested that a higher [CHL] surf in winter occurs concomitantly with a biomass increase, as a consequence of nutrient entrainment at the surface (Jolliff et al, 2008;Melo González et al, 2000;Müller-Karger et al, 1991Salmerón-García et al, 2011).…”
Section: Introductionmentioning
confidence: 99%